1991
DOI: 10.1242/dev.112.2.477
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of laminin during intestinal development

Abstract: The expression of laminin, a major glycoprotein constituent of basement membranes, was investigated in the rat developing intestine. The biosynthesis of laminin was studied after metabolic labeling of intestinal segments taken at various stages of development; the neosynthesized laminin was purified by affinity chromatography on heparin-Sepharose. Immunoblotting and immunoprecipitation experiments allowed us to analyze its constitutive chains. The data show that laminin is synthesized in very large amounts at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…4c ). In most mature tissues, however, the expression of laminin-111 is not as prominent as it is in Matrigel 64 , 65 , and different laminin isoforms, such as laminin-332 and laminin-511, are distributed across native GI tissues 47 , 48 , 66 and in our GI tissue-derived ECM hydrogels (Supplementary Fig. 4c ).…”
Section: Discussionmentioning
confidence: 93%
“…4c ). In most mature tissues, however, the expression of laminin-111 is not as prominent as it is in Matrigel 64 , 65 , and different laminin isoforms, such as laminin-332 and laminin-511, are distributed across native GI tissues 47 , 48 , 66 and in our GI tissue-derived ECM hydrogels (Supplementary Fig. 4c ).…”
Section: Discussionmentioning
confidence: 93%
“…More recently, the focus shifted onto this mesenchymal niche and the different subtypes of fibroblasts that constitute this niche in vivo ( McCarthy et al, 2020a ). Next to secreted growth factors, such as Wnt ligands and R-spondin, data support a strong role for these mesenchymal cells in controlling the composition of the extracellular matrix in vivo and, there­fore, points to a potential role for the creation of a niche ( Ormestad et al, 2006 ; Simo et al, 1991 ; Simon-Assmann et al, 1994 , 1990 ). Here, we show that both the interstitial matrix (collagen I) as well as the basement membrane matrix (Matrigel/laminin) support the long-term growth of the intestinal epithelium with the presence of all major cell lineages.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, many efforts have been made to recapitulate events leading to crypt morphogenesis and the formation of stem cell compartments in vivo and in vitro ( Sumigray et al, 2018 ; Kwon et al, 2020 ; Yang et al, 2021 ; Serra et al, 2019 ; Chang et al, 2008 ). Earlier studies already observed a fundamental remodelling of the intestinal ECM during gut development ( Simo et al, 1991 ; Simon-Assmann et al, 1990 ). Spatial and temporal expression of the distinct laminin and integrin subunits has also been characterised in the human and murine intestines; however, its direct functional relevance on the epithelium is not well described ( Simon-Assmann et al, 1994 ).…”
Section: Introductionmentioning
confidence: 94%
“…As PhotoExM facilitates imaging of whole organoids by optical clearance while retaining the spatial localization of extracellular proteins, it allows super-resolution imaging of cell-matrix interactions. The importance of cell-matrix interactions and ECM dynamics have been well established in embryological intestinal development, [24][25][26][27][28] but have not been studied indepth with regard to their specific role in shaping and guiding organoid growth and morphogenesis. Organoid studies, rather, have broadly highlighted the need for cell−ECM interactions for colony survival and growth, as well as the need for certain proteins, specifically laminin, to facilitate intestinal crypt formation.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of laminin in intestinal development and regeneration has been shown in model organisms in vivo, as well as in organoids in vitro. [3,[24][25][26][27][28] available RNA-sequencing data from intestinal organoids, [30] and saw an increase in laminin mRNA expression at the onset of crypt formation (Figure S2a, Supporting Information), so we anticipated it would be an ideal protein to image as related to cell−ECM interactions in intestinal organoids. However, because of the high concentration of laminin in Matrigel (≈60% [31] ), technical limitations related to poor antibody penetration restricted our ability to analyze the role of laminin (Figure S2d, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%